2021
DOI: 10.3390/horticulturae7060131
|View full text |Cite
|
Sign up to set email alerts
|

Is There Daily Growth Hysteresis versus Vapor Pressure Deficit in Cherry Fruit?

Abstract: The growth of cherry fruit is generally described using a double sigmoid model, divided into four growth stages. Abiotic factors are considered to be significant components in modifying fruit growth, and among these, the vapor pressure deficit (VPD) is deemed the most effective. In this study, we investigated sweet cherry fruit growth through the continuous, hourly monitoring of fruit transversal diameter over two consecutive years (2019 and 2020), from the beginning of the third stage to maturation (forth sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to this research, there was a completely different mechanism of leaf and fruit water exchange in response to increasing water deficit in the two cultivars, which might be driven by different osmotic adjustments, cell-wall elasticity and tissue water content [35]. Recently, in the cherry fruit growth relationship with VPD, full hysteresis was found only during the maturation phase while during fruit extension phase the hysteresis was null or partial [11].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to this research, there was a completely different mechanism of leaf and fruit water exchange in response to increasing water deficit in the two cultivars, which might be driven by different osmotic adjustments, cell-wall elasticity and tissue water content [35]. Recently, in the cherry fruit growth relationship with VPD, full hysteresis was found only during the maturation phase while during fruit extension phase the hysteresis was null or partial [11].…”
Section: Introductionmentioning
confidence: 86%
“…where x is the normalized value, x is the value of the existing data, and x min and x max are the minimum and maximum values of the data, respectively [11].…”
Section: Fruit Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Zucchini et al [8] determined whether there is a daily growth hysteresis versus vapor pressure deficit in cherry (Prunus cerasus) fruit. Their results indicated that hysteresis can be employed to evaluate the initial phenological phase of fruit maturation, as a fully clockwise hysteresis curve was observable only in the fourth stage of fruit growth.…”
mentioning
confidence: 99%